Tourism-based Cultural Education - Kurniawan, Ahmad (Journal of Tourism and Creativity, 2023)
In the development of the world of education, especially in the specialization of social sciences in high schools, they do not understand the philosophy of the subjects delivered by educators. Even though based on the research findings, it shows that the world of education in Indonesia has now been juxtaposed with cultural education, but teachers still feel worried about how the achievements of the subjects given can be applied to their students. This is evidenced by direct observations to the class, asking how important the subjects they live are. They said that the knowledge they learned seemed to only be a complement to the graduation requirements for advancing to grades. With this phenomenon, it means that the curriculum model that has been arranged in such a way is only a mere contestation, so it is necessary to add a tourism-based cultured education curriculum model. This arises because seeing the enthusiasm of students when they study social science which is always associated with tourism science becomes more enthusiastic in following the whole learning process. By using the SLR (study literature review) research method, the researcher only focuses on literature review that can strengthen the researcher's argument in reviewing this research which aims to see the effect of the effectiveness of the new model style in cultural education associated with tourism science.